2019
DOI: 10.1038/s41598-019-48090-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota signatures relating to reduced memory and exploratory behaviour in the offspring of overweight mothers in a murine model

Abstract: An elevated number of women of reproductive age are overweight, predisposing their offspring to metabolic and neuropsychiatric disorders. Gut microbiota is influenced by maternal factors, and has been implicated in the pathogenesis of neurodegenerative diseases. Our aim was to explore the effects of maternal high-fat feeding on the relationship linking gut microbiota and cognitive development in the offspring. Murine offspring born to dams undergoing normal diet (NDm) and high-fat diet (HFDm) were studied at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 75 publications
6
34
0
Order By: Relevance
“…Chronic inflammation is considered an important factor in the cognitive decline [49]. It has been shown repeatedly that the increase in the content of Proteobacteria is associated with certain cognitive deficits [39,50].…”
Section: Plos Onementioning
confidence: 99%
“…Chronic inflammation is considered an important factor in the cognitive decline [49]. It has been shown repeatedly that the increase in the content of Proteobacteria is associated with certain cognitive deficits [39,50].…”
Section: Plos Onementioning
confidence: 99%
“…According to this, brain insulin resistance can be defined as failure of insulin to suppress brain glucose uptake, which is coherent with the finding of high glucose uptake under human euglycemic insulin clamp conditions. Comparing healthy lean mice of different ages, we observed that the central hypometabolic action of insulin was significant in adult and old mice, but was not present in early post-natal life (69, 92). It is plausible that brain glucose suppressing signals are not yet operative in the first period of life, to ensure sufficient energy provisions during this demanding phase of rapid brain growth.…”
Section: Emerging Mechanistic Hypotheses Leading To Preventive Perspementioning
confidence: 86%
“…Panel A shows that the development of obesity in a genetic rodent model (Zucker rat) is characterized by brain hypermetabolism both in fasting condition (dashed lines) and during oral glucose tolerance test (solid line) (59). Panel B illustrates the effect of exposure to maternal obesity, resulting in a hypermetabolic brain response to isoglycemic insulin stimulation (solid line) in very early life (70), and mild brain hypermetabolism in fasting conditions (dashed lines) (92). Panel C shows the progressive increase of brain glucose uptake in response to food presentation in inhibitory control regions (open circles) and in reward related regions (closed circles) from normal weight women to women with obesity without and with food addiction (62, 64) in adult age.…”
Section: Homeostatic Regulation Of Brain Glucose Metabolism In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Strong preclinical evidence testified an effect of the GM on brain functioning and development 10 . Following the pioneering study of Sudo and colleague 11 reporting an alteration of the hypothalamic–pituitary–adrenal (HPA) stress response in germ-free mice, data have accumulated confirming the role of the commensal microbiota in stress responsiveness 12 15 , anxiety and depression-like behaviors, and cognitive functions 16 19 . However, when studies are translated into humans, understanding the effects of GM on CNS becomes more difficult 20 .…”
Section: Introductionmentioning
confidence: 99%